Real Science Mask with QR Code to Improve The Digital Literation - Savitri, Erna Noor; Dewi, Novi Ratna; Amalia, Andin Vita; Rahmadani, Oky Eviana Putri; Kholidah, Anisia (Unnes Science Education Journal, 2021)
This research aims to develop a valid Real Science Mask with QR Code learning media. The goal to be achieved through this research in general is to produce learning media that can build a concrete learning experience and be able to improve digital literacy of science students. The research and development (RnD) method by analysis, design, development, implementation, and evaluation (ADDIE) was performed. The data collection instruments used were observation sheets, expert validation sheets, and questions. The teaching and learning instruments were declared feasible and ready for application with a few revisions based on the validation results. Aspects that are considered in the feasibility test of the Real Science Mask with QR Code media are relevance, efficiency, effectiveness, flexibility, interface, suitability of material with digital and cognitive literacy skills, and media function. Real Science Mask with QR Code is a specially designed learning media that has been tested feasible and valid to improve digital literacy of science students.